1990
DOI: 10.1093/oxfordjournals.jbchem.a123144
|View full text |Cite
|
Sign up to set email alerts
|

Osmolarity-Dependent Characteristics of [3H]Ryanodine Binding to Sarcoplasmic Reticulum1

Abstract: While many reports have shown that Ca2+ alone causes ryanodine binding to the heavy fraction of the sarcoplasmic reticulum (HFSR), our results demonstrate that caffeine or beta,gamma-methylene adenosine triphosphate (AMPOPCP) in addition to Ca2+ is necessary for ryanodine binding, although Ca2+ is indispensable for it. While clarifying the reasons for this discrepancy, we found that a high osmolarity of the reaction medium, but not ionic strength, is a crucial factor. In a hypertonic solution containing 1 M Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
1

Year Published

1993
1993
2000
2000

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 0 publications
4
11
1
Order By: Relevance
“…There appears to be a temperature-and concentration-dependent monovalent ion effect on [ 3 H]ryanodine binding with tissue-specific response. Concentrations of KCl and/or NaCl above 0.25 M are activating at 25°C in rabbit skeletal muscle (51), bullfrog skeletal muscle (53), smooth muscle (47), and, as reported here, in acinar cells. At 37°C, concentrations of KCl and/or NaCl are activating in rat heart muscle, but inhibitory in rabbit skeletal muscle sarcoplasmic reticulum (52).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…There appears to be a temperature-and concentration-dependent monovalent ion effect on [ 3 H]ryanodine binding with tissue-specific response. Concentrations of KCl and/or NaCl above 0.25 M are activating at 25°C in rabbit skeletal muscle (51), bullfrog skeletal muscle (53), smooth muscle (47), and, as reported here, in acinar cells. At 37°C, concentrations of KCl and/or NaCl are activating in rat heart muscle, but inhibitory in rabbit skeletal muscle sarcoplasmic reticulum (52).…”
Section: Resultssupporting
confidence: 75%
“…The effect of dimethyl sulfoxide, used as a vehicle in studies with FK506 and bastadins, was examined and found to inhibit the equilibrium binding of 6 nM [ 100 -200 M when equilibrium binding was determined at the nonsaturating concentration of 6 nM [ 3 H]ryanodine; whereas, FK506 was much less efficacious, producing a 2.0-fold increase in occupancy at 300 M (Fig. 8) Since NaCl, at least partially, substituted for KCl, but sucrose, at a concentration close to physiologic molar equivalents, did not, the increase in [ 3 H]ryanodine binding at 25°C appears to be dependent on ionic strength as reported for smooth muscle (47), and not on osmolarity of the binding media, as reported for bullfrog skeletal muscle (53). There appears to be a temperature-and concentration-dependent monovalent ion effect on [ 3 H]ryanodine binding with tissue-specific response.…”
Section: Resultssupporting
confidence: 52%
“…Caffeine sensitized [3H]ryanodine binding to Ca 2+ activation with only slight increase in the maximal binding, in contrast to the effect of AMPOPCP. The effect of caffeine was weaker in 0.17 M NaCl-medium than that in 1 M NaCl-medium or that with SR vesicles in 0.17 M and 1 M NaC1 medium [12,16]. The combined effect of AMPOPCP and caffeine appeared potentiating in 0.17 M NaCI medium, while it was additive in 1 M NaC1 medium.…”
Section: Resultsmentioning
confidence: 82%
“…To know the functions of t~-and I]-RyRs in vivo, determinations are desirable under an isotonic condition, e.g. in 0.17 M NaCI or KC1 medium, because some differences in ryanodine binding to SR vesicles with or without CHAPS/phospholipids have been reported between 1 M and 0.17 M NaC1 media [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in KCl or NaCl concentration stimulates Ca 2ϩ release from SR vesicles and increases [ 3 H]ryanodine binding (7)(8)(9)(10)(11). A stimulation of [ 3 H]ryanodine binding (9) and slowing of single channel gating (12) by sucrose in the presence of salt suggests that the osmolarity and viscosity of the assay media may play a role in determining channel activity. Anions often classified as chaotropic ions (Cl0 4 Ϫ , SCN Ϫ , I…”
mentioning
confidence: 99%